Whole-brain mapping of the direct inputs and axonal projections of POMC and AgRP neurons - Wang, Daqing; He, Xiaobing; Zhao, Zhe; Feng, Qiru; Lin, Rui; Sun, Yue; Ding, Ting; Xu, Fuqiang; Luo, Minmin; Zhan, Cheng (Frontiers in Neuroanatomy, 2015)
Pro-opiomelanocortin (POMC) neurons in the arcuate nucleus (ARC) of the hypothalamus and nucleus tractus solitarius (NTS) of the brainstem play important roles in suppressing food intake and maintaining energy homeostasis. Previous tract-tracing studies have revealed the axonal connection patterns of these two brain areas, but the intermingling of POMC neurons with other neuron types has made it challenging to precisely identify the inputs and outputs of POMC neurons. In this study, we used the modified rabies virus to map the brain areas that provide direct inputs to the POMC neurons in the ARC and NTS as well as the inputs to the ARC AgRP neurons for comparison. ARC POMC neurons receive inputs from dozens of discrete structures throughout the forebrain and brainstem. The brain areas containing the presynaptic partners of ARC POMC neurons largely overlap with those of ARC AgRP neurons, although POMC neurons receive relatively broader, denser inputs. Furthermore, POMC neurons in the NTS receive direct inputs predominantly from the brainstem and show very different innervation patterns for POMC neurons in the ARC. By selectively expressing fluorescent markers in the ARC and NTS POMC neurons, we found that almost all of their major presynaptic partners are innervated by POMC neurons in the two areas, suggesting that there are strong reciprocal projections among the major POMC neural pathways. By comprehensively chartering the whole-brain connections of the central melanocortin system in a cell-type-specific manner, this study lays the foundation for dissecting the roles and underlying circuit mechanisms of specific neural pathways in regulating energy homeostasis.